UKRAINECENTRIC OF SCIENTIFIC WORK OF NATALIА KUZIAKINA - Ковальчук, Г. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article on a historically biographic background was scientific inheritance analyzed of the prominent Ukrainian and Russian literary critic and specialist in drama study ХХ of professor Natalia Kuziakina, was underlined expressive ukrainecentric of her research, special concentration on dramaturgy of period of the Shot up Revival. The scientist, without regard to ideological pressure on her, did an invaluable contribution to development of cognition of the Solovki pages of the Ukrainian culture subjected to repression.